If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6a + 8 = 0 Reorder the terms: 8 + -6a = 0 Solving 8 + -6a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -6a = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -6a = 0 + -8 -6a = 0 + -8 Combine like terms: 0 + -8 = -8 -6a = -8 Divide each side by '-6'. a = 1.333333333 Simplifying a = 1.333333333
| -1+10x=15y | | 1344=L(8)(12) | | 0.003x=6 | | 6x^3-7x^2+2x+8= | | 35(2x-1)=4(x-4)+3x | | 8x+y-5=0 | | 5x+6+9x+5= | | 18-3v=42 | | 12x+b=180 | | 10x+5x-20=25 | | 2x+(5*5)=25 | | -5(-4m-8)=-2m-26 | | 78y+45=13 | | (2x+24)+(4x+36)=180 | | -w-7=-74 | | -28+y=-3 | | f(x)=x^2-64 | | 5X-(3X-2)=28 | | logx(2)=96 | | 4x^4-x^3-36x^2-111x+30=0 | | 3x+4=x+23 | | 100+9x=210+6x | | 3(y-2)=2(y+5) | | f(5)=3x^2-6x+4 | | 27x+13y+91z=667 | | 27x+6y=17 | | 135+23x=1+45x | | y-12=2 | | 4(-3v-1)-4=88 | | -6-5y=13 | | 35y+7=17 | | (2x+1)(x-5)=2x^2-1 |